Superior-segment Bilateral Facet Violation in Lumbar Transpedicular Fixation, Part III: A Biomechanical Study of Severe Violation. Issue 9 (1st May 2020) - Xu, Yunfeng; Le, Xiaofeng; Zhang, Qi; Kuai, Shengzheng; Leng, Huijie; Duan, Fangfang; Shi, Zhan; Liu, Bo; He, Da; Lang, Zhao; Wu, Jingye; Wang, Ling; et al.
Abstract : Mini: In controls, adjacent-level range of motion (ROM) did not change relative to noninstrumented spine at each moment. In severe violation, flexion-extension and rotation ROM of adjacent vertebrae decreased at each moment (7.5, 6.0, 4.5 Nm); lateral bending ROM decreased at 4.5 Nm. Significant differences in movements were found except lateral bending (7.5 Nm). Study Design: This is an in vitro biomechanical study. Objectives: This study aimed to investigate the biomechanical variations of lumbar spine motor units after bilateral facet joint severe violation in cadaver specimens and analyze the biomechanics under different moments. Summary of Background Data: The incidence of facet joint violation (FJV) is highly variable, and one of the most important factors is the lack of awareness of protection. Until now, the biomechanical effects of FJV remain unclear. Methods: Biomechanical testing was performed on 12 human cadaveric spines under flexion-extension, lateral bending, and axial rotation loading. After intact analysis, pedicle screws were inserted at L5, and the biomechanical testing was repeated. Full range of motion (ROM) at the proximal adjacent levels under different moments was recorded and normalized to the intact (100%) noninstrumented spine. The relative ROM changes were compared between the control and severe violation groups. Results: The adjacent-level ROM (flexion-extension, lateral bending, axial rotation) did not change significantly in the control group at each moment (7.5, 6.0, 4.5 Nm) compared with the intact noninstrumented spine. In the severe violation group, the supradjacent-level ROM decreased significantly under all moments relative to the intact noninstrumented spine ( P  < 0.05) except for the ROM of lateral bending at moments of 7.5 and 6.0 Nm. When comparing the ROM between the two groups, there were significant differences in all movements except lateral bending at 7.5 Nm. Conclusion: When superior-segment bilateral facet joints are severely violated by screws, the flexion-extension and axial rotation ROM of adjacent vertebrae decreases at each moment (7.5, 6.0, 4.5 Nm), and the lateral bending ROM decreases at 4.5 Nm. Level of Evidence: N/A